Oxytocin Attenuates Methamphetamine-Induced Apoptosis via Oxytocin Receptor in Rat Hippocampal Neurons - Li, Chunli; Wang, Haipeng; Wang, Min; Chen, Chunyun; Bai, Fei; Ban, Mengqi; Wu, Chunfu (Frontiers in Pharmacology, 2021)
Methamphetamine (METH) is a highly neurotoxic psychoactive substance that can directly damage the central nervous system through prolonged use. Oxytocin (OT) has attracted much attention because of its neuroprotective effect. The purpose of this study was to investigate whether OT is neuroprotective against METH-induced damage in rat hippocampal neurons. Our results revealed that pre-incubation with OT significantly prevented the damage of METH to hippocampal neurons, including the decrease of mitochondrial membrane potential and the increase of ROS (reactive oxygen species). OT pre-incubation attenuated the up-regulation of Cleaved-Caspase-3 expression and the down-regulation of Bcl-2/Bax expression induced by METH. Pre-incubation with OT prevented the decrease in oxytocin receptor density and P-CREB (phosphorylation of cAMP-response element binding) expression induced by METH in rat hippocampal neurons. Moreover, Pre-incubation of atosiban (ATO) significantly prevented these changes. In conclusion, our study proved that pre-administration of OT could significantly attenuate hippocampal neuron apoptosis induced by METH. Oxytocin receptor activation is involved in the preventive effect of OT on METH-induced apoptosis in rat hippocampal neurons.